Pengaruh Sumber Informasi dan Kualitas Website terhadap Kepercayaan Pelanggan dalam Menentukan Keputusan Bertransaksi pada E-commerce (Studi pada Pelanggan E-commerce di Indonesia) - Piarna, Rian (Jurnal Aplikasi Manajemen, 2014)
The purposes of this research are to analyze the influence of information source and website quality on e-commerce's trust and customer's decision on e-commerce transaction This research conducted by taken 150 samples on e-commerce customers in Indonesia. Data collection is online questionnaire and analysis data used SEM. The result showed that information source directly not influence on trust and transaction decision. Website quality has significant influence on transaction dealing.